Pengawasan Legislatif Dalam Penyelenggaraan Pemerintahan Daerah Di Kota Tangerang Provinsi Banten - Susanto, Turidi; Rowa, Hyronimus; Tahir, Baharudin (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2025)
The phenomenon used as the object of research is the supervision carried out by the Legislature or the Tangerang City People's Representative Council in the implementation of local government in Tangerang City. The implementation of supervision is a manifestation of one of the functions inherent in the body of each Legislative Member. The supervisory function of the DPRD is the observation and direction of an action that is based on the applicable legal provisions. The supervisory function of the DPRD is used by the executive to process the examination, monitoring and evaluation of the implementation of public policies with the aim of ensuring the success of policies and programs that have been implemented in accordance with applicable laws. The research was conducted using a descriptive qualitative method approach with a total of 6 informants. The results of the research are (1) Supervision carried out by the Tangerang City DPRD in the implementation of local government in Tangerang City has been running optimally, this can be seen from the improving performance of bureaucrats in Tangerang City; (2) Factors that hinder the supervision of the Tangerang City DPRD in the implementation of local government in Tangerang City are Human Resources and Budget Resources; (3) The efforts of the Tangerang City DPRD in overcoming the factors that hinder the implementation of local government of the Tangerang City DPRD are by coordinating, communicating and socializing all programs planned by the Tangerang City Government.